Cross-regional analysis of banking efficiency drivers. Issue 18 (15th April 2021) - Paulet, Elisabeth; Mavoori, Hareesh
ABSTRACT: The banking industry plays a crucial role in any economy by providing diverse services aimed at enhancing economic growth. In recent decades, this sector has been transformed due to financial liberalization and new regulatory rules. Therefore, measuring the efficiency of banking institutions is critically important to identify the evolution of efficiency drivers for banks. Based on a sample of 90 individual banks from four different world regions (Europe, US, China, and India), this paper conducts data envelopment, stochastic frontier and anova analyses to measure cost efficiency over a 15-year period (2002–2016). While the overall liberalization of financial markets seems to induce a convergence among efficiency strategies privileging cost minimization to improve efficiency, the existence of state intervention in China and India nuances our results. State owned banks base their efficiency more on maximization of their potential revenue than on controlling costs. On the contrary, their private peers are more similar to Western peers.